Packaging laminate
Patent Information
- Application Number
- JP2024042381
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2024-03-18
- Publication Date
- 2025-02-14
AI Technical Summary
【0012】 本発明の包装用積層体は、リグラインド層中に鉄粉(B)とエチレン·ビニルアルコール共重合体(C)とを含有しているが、このリグラインド層には多くのオレフィン系樹脂(A)を含んでいる。即ち、生産工程で生成する廃材(鉄粉及びエチレン·ビニルアルコール共重合体を含んでいる)がリグラインド層の形成に使用されるのであるが、本発明では、この廃材が多量のバージンのオレフィン系樹脂により希釈されており、該リグラインド層中には、鉄粉(B)は、オレフィン系樹脂(A)100質量部当り0.1~8.0質量部、エチレン·ビニルアルコール共重合体(C)は、オレフィン系樹脂(A)100質量部当り0.1~14.0質量部の量で存在している。この結果、リグラインド層での発泡を有効に抑制することができる。
Smart Images

Figure 2025022713000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a packaging laminate having a regrind layer containing iron powder. [Background technology]
[0002] It has long been known that iron has oxygen absorbing properties. That is, iron reacts with moisture to produce divalent ferric hydroxide, which then reacts with oxygen to produce ferric oxide (Fe2O3), which absorbs oxygen. Taking advantage of this property, iron is used as an oxygen scavenger in the field of packaging materials, suppressing deterioration of packaged materials caused by oxygen, thereby ensuring quality assurance and improving shelf life.
[0003] For example, Patent Document 1 discloses an oxygen absorber for blending with resins, which is composed of a mixed powder containing iron powder, a metal halide, and an alkaline substance, and proposes blending such an oxygen absorber with various thermoplastic resins to prepare a resin composition, and using the resin composition as an intermediate layer in the wall of a container. Furthermore, Patent Document 2 proposes a multi-layer plastic container characterized by having a layer of a resin composition in which a gas barrier resin is blended with an oxygen scavenger and a water absorbing agent. Furthermore, Patent Document 3 also discloses an oxygen absorber (also called an oxygen scavenger) consisting of iron powder and a metal halide, and proposes molding a film or sheet formed from a thermoplastic resin composition in which this oxygen absorber is dispersed into a container. The containers disclosed in these patent documents all exhibit high oxygen barrier properties through oxygen absorption, and prevent the contents from deteriorating due to oxidation.
[0004] Recently, from the viewpoint of environmental protection and resource saving, recyclability is also required in the field of packaging materials, and mono-materialization of materials is being demanded. In other words, if plastic containers are molded using as many similar resins as possible, they can be easily collected and reused as containers or other plastic molded products.
[0005] From this perspective, multi-layer containers that have an oxygen absorbing layer made of an oxygen absorbent (or oxygen scavenger) containing iron powder are attracting attention. Iron powder is an inorganic material, so it can be easily separated from resins, and it also exists naturally, so it does not have a negative impact on the environment. Another advantage is that it does not generate odorous substances such as aldehydes when absorbing oxygen.
[0006] The oxygen barrier properties of the oxygen absorbing layer described above are called active barrier properties because they are based on the reaction between iron powder and oxygen. Since this property wears off as the iron powder reacts with oxygen, it is often used in the molding of containers in a multi-layer structure that also uses an oxygen barrier resin that always exhibits a constant oxygen barrier property, called passive barrier property.
[0007] However, it has been found that iron powder used as an oxygen absorber or deoxidizer as described above causes unexpected problems when used in combination with ethylene-vinyl alcohol copolymer (EVOH), a typical oxygen barrier resin. That is, in a molded body having a multi-layer structure including an oxygen barrier layer formed from EVOH or the above-mentioned oxygen absorbing layer, scrap such as burrs generated during molding is often mixed with virgin resin and reused. According to the research of the present inventors, when iron powder and EVOH coexist in such a regrind layer, foaming often occurs, which causes a decrease in oxygen barrier properties and a defective appearance of the container. Therefore, it is necessary to prevent such foaming, but the fact is that foaming generated in such a regrind layer has not been considered at all in the past, including the above-mentioned Patent Documents 1 to 3. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 5378639 [Patent Document 2] Special Publication No. 4-60827 [Patent Document 3] Special Publication No. 6-57319 Summary of the Invention [Problem to be solved by the invention]
[0009] Therefore, an object of the present invention is to effectively suppress foaming in a regrind layer in a packaging laminate having a regrind layer containing iron powder and an ethylene-vinyl alcohol copolymer. [Means for solving the problem]
[0010] According to the present invention, there is provided a packaging laminate having a regrind layer, comprising: The regrind layer contains, in addition to the olefin resin (A), 0.1 to 8.0 parts by mass of iron powder (B) and 0.1 to 14.0 parts by mass of an ethylene-vinyl alcohol copolymer (C) per 100 parts by mass of the olefin resin (A).
[0011] In the packaging laminate of the present invention, the following aspects are preferably adopted. (1) In the regrind layer, the mass ratio (B / C) of the iron powder (B) to the ethylene-vinyl alcohol copolymer (C) is 1.0 or less. (2) The inner and outer layers include olefin-based resin layers, and an oxygen barrier layer and an oxygen absorbing layer are included as intermediate layers between the inner and outer layers in addition to the regrind layer. (3) A white resin layer containing a white pigment is provided. (4) The entire laminate, including the olefin resin (A) present in the regrind layer, contains an olefin resin in an amount of 80.0% by mass or more, particularly 83.5% by mass or more. (5) The laminate contains 80 parts by mass or more of olefin-based resin, and contains less than 16.9 parts by mass of resins other than olefin-based resins, per 100 parts by mass of the laminate, and contains less than 5 parts by mass of iron powder. (6) It has the form of a film or sheet. (7) It has the form of a bag. (8) Contains metal halides and alkaline compounds. Effect of the Invention
[0012] The packaging laminate of the present invention contains iron powder (B) and ethylene-vinyl alcohol copolymer (C) in the regrind layer, and this regrind layer contains a large amount of olefin resin (A). That is, waste material (containing iron powder and ethylene-vinyl alcohol copolymer) generated in the production process is used to form the regrind layer, but in the present invention, this waste material is diluted with a large amount of virgin olefin resin, and the regrind layer contains 0.1 to 8.0 parts by mass of iron powder (B) per 100 parts by mass of olefin resin (A) and 0.1 to 14.0 parts by mass of ethylene-vinyl alcohol copolymer (C) per 100 parts by mass of olefin resin (A). As a result, foaming in the regrind layer can be effectively suppressed.
[0013] It is presumed that such foaming in the regrind layer is due to the evaporation of gas generated by thermal degradation of ethylene-vinyl alcohol copolymer (EVOH) and water generated by dehydration reaction, and iron is considered to play a catalytic role in promoting such thermal degradation and reaction of EVOH. That is, since the EVOH in the regrind layer is contained in the waste material and is repeatedly subjected to heat history in the presence of iron, it is considered that the catalytic effect of iron promotes the thermal degradation and dehydration reaction of EVOH, generating gas and causing foaming. However, in the present invention, iron and EVOH are diluted by a large amount of olefin resin, and as a result, the catalytic effect of iron is diluted, and it is considered that the thermal degradation and dehydration reaction of EVOH are effectively suppressed and foaming is prevented.
[0014] As can be understood from the fact that the regrind layer contains iron and EVOH, the packaging laminate of the present invention has an oxygen absorbing layer containing iron and an oxygen barrier layer containing EVOH, and as a result has excellent oxygen barrier properties and can effectively prevent oxidative deterioration of the packaged material.
[0015] Furthermore, the packaging multilayer structure of the present invention is suitable for mono-material production, and has excellent recyclability, for example, when the entire laminate contains 80.0% by mass or more, particularly 83.5% by mass or more of an olefin-based resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] As described above, the packaging laminate of the present invention has an oxygen absorbing layer containing iron and an oxygen barrier layer containing EVOH, which exist as intermediate layers between the inner and outer olefin resin layers, and further has a basic layer structure including a regrind layer as an intermediate layer, and further has other layers as necessary. Each layer will be described below in order.
[0017] Inner and outer layers (olefin resin layers); The olefin-based resin layers constituting the inner and outer layers are formed from a known olefin-based resin. Examples of such olefin-based resins that can be used include known resins that have conventionally been used as packaging materials, such as ethylene-based resins such as low-density polyethylene and high-density polyethylene; propylene-based resins such as polypropylene and random polypropylene; olefin-based copolymers such as poly-1-butene, poly-4-methyl-1-pentene, or random or block copolymers of α-olefins such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene; and cyclic olefin copolymers disclosed in, for example, JP-A No. 2007-284066. In the present invention, ethylene-based resins and propylene-based resins are preferably used, and ethylene-propylene block copolymers are most suitable from the standpoint of heat resistance, strength, and the like.
[0018] From the viewpoint of reducing the environmental load, it is preferable that the raw materials or a part of the raw materials of the olefin resin are not only derived from petroleum but also from chemically recycled materials using monomerization technology such as gasification or oilification of waste plastics, or from biomass materials such as plant-derived materials. The degree of biomass can be measured by measuring the radioactive carbon concentration. Furthermore, when producing the olefin resin, it is preferable to produce it using a catalyst system that does not use SVHC substances (Substances of Very High Concern under the European Registration, Evaluation, Authorization and Restriction of Chemicals (REACH) regulation) such as phthalate ester compounds in the polymerization stage from the raw materials.
[0019] Gas barrier layer; In the present invention, an ethylene-vinyl alcohol copolymer (EVOH) exhibiting passive barrier properties is used as the gas barrier layer.
[0020] As the above-mentioned EVOH, a saponified copolymer obtained by saponifying an ethylene-vinyl acetate copolymer having an ethylene content of generally 20 to 60 mol%, particularly 25 to 50 mol%, to a degree of saponification of 96 mol% or more, particularly 99 mol% or more, is suitable.
[0021] Oxygen absorbing layer; The oxygen absorbing layer is a layer containing a publicly known oxygen absorbent (also called an oxygen scavenger). That is, the oxygen absorbent contains iron powder, a metal halide, and an alkaline substance, and the oxygen absorbing layer is formed by dispersing such an oxygen absorbent in an olefin resin.
[0022] As described above, in such oxygen absorbents, iron is a metal that exhibits oxygen absorbing properties (oxygen capture), and usually has a BET specific surface area of 0.5 m. 2 / g or more. As such iron powder, known iron powders such as reduced iron powder, atomized iron powder, electrolytic iron powder, and carbonyl iron powder can be used, but reduced iron powder is preferably used because of its high oxygen absorption capacity. That is, reduced iron powder is obtained by reducing iron ore and has a large specific surface area. Furthermore, among reduced iron powders, rotary reduced iron powder is particularly preferable because of its high purity.
[0023] The metal halide functions as an auxiliary agent that promotes the oxygen absorption reaction, and is a halide of various metals (e.g., alkali metals, alkaline earth metals, copper, zinc, iron, etc.), and examples of such metal halides include sodium chloride, sodium bromide, sodium iodide, potassium chloride, potassium bromide, potassium iodide, calcium chloride, magnesium chloride, barium chloride, etc. In particular, sodium chloride is most suitable in terms of performance as an auxiliary agent, cost, etc.
[0024] Such metal halides may be used in small amounts compared to the iron powder, for example, in an amount of 0.1 to 10 parts by mass, particularly 1 to 5 parts by mass, per 100 parts by mass of iron powder.
[0025] Furthermore, the alkaline substance absorbs water and promotes the oxygen absorption reaction by the iron powder, and examples of the alkaline substance that can be used include magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, etc. In particular, non-carbonate compounds are preferred in terms of avoiding foaming, and slaked lime (calcium hydroxide) and quicklime (calcium oxide) are preferably used.
[0026] Such an alkaline substance may be used in a small amount compared to the iron powder, for example, in an amount of 0.5 to 2 parts by mass, particularly 1 to 2 parts by mass, per 100 parts by mass of iron powder.
[0027] In the present invention, the oxygen absorbent described above is preferably one described in, for example, Patent Document 1. In particular, one having a half-width of the peak of the iron (110) plane measured by powder X-ray diffraction method (Co-Kα) of 0.20° / 2θ or less is preferable in that it suppresses the generation of hydrogen as a by-product of the oxygen absorption reaction.
[0028] The oxygen absorbent as described above is appropriately pulverized and dispersed in an olefin resin as a mixed powder having an average particle size (median diameter) of about 1 to 40 μm. Such an olefin resin is also used to form the inner and outer layers, and from the viewpoint of mono-materialization in particular, it is preferable to use the same type of olefin resin as the inner and outer layers. For example, when the inner and outer layers are formed of polypropylene, it is optimal to use polypropylene for the oxygen absorbing layer.
[0029] In such an oxygen absorbing layer, a mixed powder of an oxygen absorbent is dispersed in an olefin resin so that the iron powder concentration is 29% by mass or more, particularly about 29 to 60% by mass.
[0030] It is also possible to mix the above-mentioned EVOH in the oxygen absorbing layer and use it as an oxygen absorbing barrier layer. In this case, the above-mentioned oxygen barrier layer of EVOH can be omitted, which is advantageous in terms of ensuring high oxygen barrier properties by reducing the number of layers of the laminate. However, when iron powder as an oxygen absorbent and EVOH coexist in the same layer, deterioration of EVOH and dehydration reaction tend to be promoted, so in the present invention, it is preferable that the oxygen absorbent (iron powder) and EVOH exist in different layers. In other words, it is preferable that they exist functionally separated in an active barrier layer and a passive barrier layer.
[0031] Regrind layer; The packaging laminate of the present invention has a regrind layer to effectively utilize waste materials, but this regrind layer is a pre-consumer material, and is a layer formed using waste materials generated in the manufacturing process before the product is delivered to the consumer, particularly waste materials (scrap) generated in the production process of the same product in a factory. For example, waste materials generated during deburring in the molding process (called trim) and waste materials generated during punching (called skeleton) are reused.
[0032] Therefore, the regrind layer necessarily contains the oxygen absorber and EVOH. Therefore, the iron powder used as the oxygen absorber and EVOH coexist in the regrind layer. That is, the EVOH in this layer is subjected to a thermal history at a temperature above its melting point during molding of the laminate (extrusion molding, injection molding, etc.), and so it will again be subjected to a thermal history at a temperature above its melting point. That is, in this regrind layer, the EVOH that has once been subjected to a thermal history is subjected to a second thermal history in the presence of the iron powder, and as a result, the thermal degradation and dehydration reaction of the EVOH progresses significantly, making it more likely to foam.
[0033] In the present invention, in order to prevent foaming in the regrind layer, the above-mentioned waste material is diluted with a large amount of olefin resin and used to form the regrind layer. Specifically, the regrind layer contains 0.1 to 8.0 parts by mass, preferably 0.4 to 7.7 parts by mass, and more preferably 0.4 to 6.0 parts by mass of iron powder (B) per 100 parts by mass of olefin resin (A), and contains 0.1 to 14.0 parts by mass, preferably 0.7 to 13.3 parts by mass, more preferably 0.7 to 10.0 parts by mass, and particularly 2.0 to 10.0 parts by mass of ethylene-vinyl alcohol copolymer (C). That is, the above-mentioned waste material (scrap) contains an olefin resin, and the waste material is mixed with a virgin olefin resin so as to satisfy the above-mentioned ratio, and used as a resin composition for the regrind layer for molding the packaging laminate. In this way, foaming can be effectively prevented by diluting and adjusting the concentration of the waste material (particularly iron powder and EVOH) present in the regrind layer.
[0034] For example, if the amount of iron powder or EVOH is greater than the above range, foaming occurs, resulting in problems such as delamination between layers and noticeable poor appearance due to foaming. On the other hand, if the amount of iron powder or EVOH is less than the above range, foaming does not occur, but there is no particular advantage, and the excessive use of virgin olefin resin results in increased costs and unnecessary thickening of the laminate.
[0035] In the present invention, it is preferable that the mass ratio (B / C) of iron powder (B) to EVOH (C) is adjusted to be 1.0 or less, preferably 0.1 to 0.8, so that the amounts of iron powder and EVOH in the regrind layer satisfy the above ranges. That is, if there is an excess of iron powder relative to the EVOH, foaming is likely to occur.
[0036] In the present invention, in order to ensure that the amounts of iron powder and EVOH in the regrind layer are within the above-mentioned ranges, it is necessary to set the amount of virgin polyolefin used to dilute the waste material within a certain range, and at the same time, to design the layers so that the thicknesses of the oxygen absorbing layer and the EVOH layer contained in the laminate are within certain ranges. This should be easily understood by those skilled in the art.
[0037] Other layers; In addition to the above-mentioned basic layer, the packaging laminate of the present invention may contain other layers, such as an adhesive layer and a white resin layer, as necessary, and the above-mentioned regrind layer naturally contains the resins and ingredients contained in these layers, although in small amounts.
[0038] The adhesive layer is a layer used to increase the adhesive strength between the inner and outer layers, the oxygen absorbing layer and the EVOH layer and to prevent delamination between the layers, and is formed using a known adhesive resin. Examples of such adhesive resins include resins containing carbonyl groups (>C=O) in the main chain or side chain in an amount of 1 to 100 meq / 100 g resin, particularly 10 to 100 meq / 100 g resin. Specific examples of such adhesive resins include olefin resins graft-modified with carboxylic acids such as maleic acid, itaconic acid, and fumaric acid, or their anhydrides, amides, and esters; ethylene-acrylic acid copolymers; ionically cross-linked olefin copolymers; and ethylene-vinyl acetate copolymers.
[0039] The white resin layer is provided to conceal the color of the oxygen absorbing layer containing iron powder, which is black in color. Although this varies depending on the application, generally, the oxygen absorbing layer containing iron powder and the regrind layer are provided between two white resin layers, thereby providing effective concealment. Such a white resin layer is a layer in which a white pigment such as titanium oxide (titanium white) or zinc oxide (zinc white) is dispersed in an olefin resin, and typically contains the white pigment in an amount of 4 to 25 parts by mass per 100 parts by mass of the olefin resin. Therefore, such a white pigment is also contained in the regrind layer (or waste material) described above.
[0040] layer design; Examples of the layer structure of the packaging laminate of the present invention are shown below. In the following examples, the following abbreviations are used: Additionally, the inside is the side that comes into contact with the material being packaged, and the outside is the side opposite the inside. OP: Olefin resin layer EV: Ethylene-vinyl alcohol copolymer (EVOH) layer Abs: Oxygen absorption layer REG: Regrind layer AD:Adhesive layer WH: White resin layer
[0041] (inside) OP / Abs / AD / EV / AD / REG / OP (outside) (inside) OP / AD / EV / AD / Abs / REG / OP (outside) (inside) OP / WH / Abs / AD / EV / AD / REG / WH / OP (outside) (Inside) OP / WH / Abs / AD / EV / AD / REG / WH(Outside) (Inside) WH / Abs / AD / EV / AD / REG / WH(Outside) (inside) OP / WH / REG / AD / Abs / AD / EV / AD / WH / OP (outside) (inside) OP / WH / AD / EV / AD / Abs / REG / WH / OP (outside)
[0042] The above layer structure is an example, and is not limited thereto, and for example, it is possible to provide a plurality of EVOH layers or oxygen absorbing layers. In addition, each layer may be colored by adding a pigment or the like, if necessary. In such a layer structure, each layer is set to a thickness that satisfies the characteristics required for the laminate depending on the application, but the amount of oxygen absorber (iron powder) and EVOH in the regrind layer naturally depends on the thickness of the oxygen absorbing layer and EVOH layer. Therefore, as mentioned above, it is necessary to set the thickness of the oxygen absorbing layer and EVOH layer so that the amount of iron powder and EVOH in the regrind layer satisfies the above-mentioned conditions.
[0043] Furthermore, in the present invention, provided that the amounts of iron powder and EVOH satisfy the above-mentioned conditions, it is preferable that the thickness of the regrind layer is 10% to 90%, particularly 15% to 80%, of the layer thickness of the laminate. If the regrind layer is too thin, the advantage of effective use of waste materials is reduced, and if it is too thick, poor appearance due to foaming becomes significant. Furthermore, in terms of flavor of the contents, it is preferable to provide the regrind layer on the outer side of the container than the EVOH layer. This is because the regrind layer has a large heat history and there is a concern of the generation of a resin deterioration odor, but this can be reduced by the EVOH layer.
[0044] From the viewpoint of recyclability, it is preferable that the amount of the olefin-based resin used in the packaging laminate of the present invention is adjusted so that the content of the olefin-based resin in the entire laminate is 80.0 mass% or more, particularly 83.5 mass%, and it is furthermore optimal that all the olefin-based resins are the same type. By making the laminate into a mono-material, sufficient recyclability can be realized. For example, iron powder has a large specific gravity and can be easily separated from the used packaging laminate.
[0045] The packaging laminate of the present invention is formed into a film or sheet by known forming means such as extrusion molding or injection molding, and in the case of a film, it can be made into a bag by taking advantage of the heat sealability of the olefin resin of the inner layer, and can be used practically as a bag-shaped container (pouch), or can be used as a lid material for a cup-shaped container. In addition, a sheet-shaped product can be formed into a cup shape by compressed air forming, vacuum forming, plug-assist forming, or the like, and used as a cup container. Furthermore, the laminate of the present invention can be formed into a tube or bottle shape by tube forming or blow molding for use. EXAMPLES
[0046] The present invention will now be further illustrated by the following non-limiting examples.
[0047] <Forming of multi-layer sheets and containers> Using a multilayer sheet molding machine, each resin was melt-kneaded in a single-screw extruder, extruded into a sheet from a T-die at a T-die temperature of 230°C, solidified by contacting it with a cooling roll, and wound up to form a multilayer sheet with a thickness of 500 μm. The layer structure is, from the outside, PP layer 85μm / regrind layer 130μm / adhesive layer 10μm / EVOH layer 15μm / adhesive layer 10μm / oxygen absorbing layer 30μm / PP layer 220μm. The resin used will be described later. The resulting multilayer sheet was heated to 145° C. and plug-assisted vacuum and pressure forming was performed to form a container (a multilayer tray with a flange).
[0048] The container dimensions are as follows: Flange outer diameter; Long axis: 155mm x short axis: 120mm Caliber; Long axis: 135mm x short axis: 100mm Bottom outer diameter; Long axis: 115mm x short axis: 90mm, height 35mm
[0049] <Evaluation> The appearance of the resulting multilayer sheet and container was evaluated. The evaluation was performed by visually observing the surface condition of the multilayer sheet and the container during molding, and by observing the cross section. The cases where no foaming was observed in either the multilayer sheet or the container were rated as ⊚, the cases where no foaming was observed in the multilayer sheet were rated as ◯, and the cases where foaming was observed in the multilayer sheet were rated as x.
[0050] The resin materials used to mold the container are as follows: PP layer; Ethylene-Propylene Block Copolymer MFR: 0.5g / 10min 230℃ Density: 0.90g / cm 3 adhesive layer; Maleic anhydride modified polypropylene MFR: 5.7g / 10min 230℃ Density: 0.89g / cm 3 EVOH layer; Ethylene-vinyl alcohol polymer Ethylene content: 32mol% MFR: 2.0g / 10min 190℃ Density: 1.17g / cm 3 Oxygen absorbing layer; A resin composition (iron powder-containing olefin resin) obtained by melt-kneading 29 parts by mass of oxygen absorber and 71 parts by mass of random polypropylene in a twin-screw extruder. The oxygen absorber has an apparent density of 1.86 g / cm 3The reduced iron composition is composed of 100 parts by mass of reduced iron, 2 parts by mass of sodium chloride, and 1 part by mass of calcium hydroxide. The random polypropylene has a MFR of 1.2 g / 10 min (230°C) and a density of 0.91 g / cm 3 It is. Regrind layer; A mixture of waste materials from molding (trim, skeleton) and PP resin.
[0051] <Examples 1 to 6, Comparative Example 1> The proportion of the waste material in the regrind layer was changed, and multi-layer sheets and containers were molded with various blends as shown in Table 1, and the appearance was evaluated. The evaluation results are also shown in Table 1.
[0052] [Table 1]
Claims
1. 1. A packaging laminate having a regrind layer, comprising: The regrind layer contains, in addition to an olefin-based resin (A), 0.1 to 8.0 parts by mass of iron powder (B) and 0.1 to 14.0 parts by mass of an ethylene-vinyl alcohol copolymer (C) per 100 parts by mass of the olefin-based resin (A).
2. 2. The packaging laminate according to claim 1, wherein in the regrind layer, a mass ratio (B / C) of the iron powder (B) to the ethylene-vinyl alcohol copolymer (C) is 1.0 or less.
3. 2. The packaging laminate according to claim 1, further comprising an olefin resin layer as an inner and outer layer, and an oxygen barrier layer and an oxygen absorbing layer as intermediate layers between the inner and outer layers in addition to the regrind layer.
4. 2. The packaging laminate according to claim 1, further comprising a white resin layer containing a white pigment.
5. 2. The packaging laminate according to claim 1, wherein the olefin-based resin is contained in an amount of 80.0% by mass or more in the entire laminate, including the olefin-based resin (A) present in the regrind layer.
6. 2. The packaging laminate according to claim 1, comprising 80 parts by mass or more of an olefin-based resin, less than 16.9 parts by mass of resins other than the olefin-based resin, and less than 5 parts by mass of iron powder per 100 parts by mass of the laminate.
7. 7. The packaging laminate according to claim 6, which is in the form of a film or sheet.
8. 7. The packaging laminate according to claim 6, which is in the form of a bag.
9. 7. The packaging laminate of claim 6, which comprises a metal halide and an alkaline compound.
Citation Information
Patent Citations
Sand protective belt
JP1978078639A
Information recorder and floppy disk device using the same as recording medium
JP1992060827A
Method for estimating manganese concentration in tapped steel from converter
JP1994057319A